2021
DOI: 10.1017/s2045796021000627
|View full text |Cite
|
Sign up to set email alerts
|

Does retirement trigger depressive symptoms? A systematic review and meta-analysis

Abstract: Aims Retirement is a major life transition that may improve or worsen mental health, including depression. Existing studies provide contradictory results. We conducted a systematic review with meta-analysis to quantitatively pool available evidence on the association of retirement and depressive symptoms. Methods We applied PRISMA guidelines to conduct a systematic review and meta-analysis to retrieve, quantitatively pool and critically evaluate the association between retirement and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 124 publications
(223 reference statements)
2
21
0
Order By: Relevance
“…This result is largely consistent with the results of previous studies, which argued that area-level social capital can affect an individual's health independently of individual-level social capital ( Mohnen et al, 2011 , 2015 ; Snelgrove et al, 2009 ; Sundquist & Yang, 2007 ) or SP ( Tsuji et al, 2018 ). Regarding the impact of retirement on health, our analyses provided mixed results, consistent with observations in previous studies ( Li et al, 2021 ; Odone et al, 2021 ; van der Heide et al, 2013 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result is largely consistent with the results of previous studies, which argued that area-level social capital can affect an individual's health independently of individual-level social capital ( Mohnen et al, 2011 , 2015 ; Snelgrove et al, 2009 ; Sundquist & Yang, 2007 ) or SP ( Tsuji et al, 2018 ). Regarding the impact of retirement on health, our analyses provided mixed results, consistent with observations in previous studies ( Li et al, 2021 ; Odone et al, 2021 ; van der Heide et al, 2013 ).…”
Section: Discussionsupporting
confidence: 89%
“…The impact on mental health is also controversial. As surveyed by Li et al (2021) and Odone et al (2021) , many studies have observed both beneficial and adverse effects of retirement on mental health. The same is true for the impact on physical health.…”
Section: Introductionmentioning
confidence: 99%
“…Between 1997 and 2010, the number of people suffering from mental disorders increased ( 67 ). This is particularly worrisome in old age, when deteriorating health with age, multi-morbidity and polypharmacy increase the risk of mental disorders predisposing to a suicidal act ( 68 ). A factor that increases this risk is the moment when people decide to retire.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the small number of studies included, Egger’s test and the trim-and-fill method were carried out to detect publication bias. The trim-and-fill method is a non-parametric statistical method used to estimate the number of missing studies and to assess and correct for publication bias ( 56 ).…”
Section: Methodsmentioning
confidence: 99%